How Do Teachers Solve Problem With Contradiction Information? Study of Prospective Teachers - Professional Teachers in Solving Problem Using The IDEAL Model - Annizar, Anas Ma'ruf; Sunardi; Susanto; Suwito, Abi (IKIP Siliwangi, 2023)
This research is a qualitative descriptive study which aims to describe the problem solving process of a professional teacher in finding solutions to problems of the Problem With Contradiction Information type. This research involved 1 mathematics teacher who had a professional teacher education certificate and had taught for at least 5 years (S1) and 1 mathematics teacher who had taught for at least 5 years but did not yet have a professional teacher education certificate (S2) and 1 prospective teacher who was still carrying out studies. S1 and does not yet have a professional teacher education certificate (S3). Data collection was carried out by tests and interviews. The research results showed that only S3 carried out all the IDEAL problem solving indicators and was the only research subject who realized the existence of contradictions in the given problem. Meanwhile, S1 and S2 do not look back and learn. All subjects started solving the problem by reading and making propositions from the problem given. S3 stated that he read twice, namely reading in depth and reading quickly to review the known data. S1 experienced Pythagorean priming when implementing the Making a Drawing and Backwards strategy. Meanwhile, S2 in implementing the Backwards strategy often has to do some work in his working memory so there are several steps that are not written down. S2 is aware that there is unnecessary data but considers it an open ended question. Meanwhile, S3 succeeded in stating that the question contained elements of contradiction and could not be done in the anticipating outcome and looking back steps. If you want to become a good problem solver then spend most of your time identifying and understanding problems and then determining how to work. Good problem solvers are not in a hurry but are still effective in solving problems. You even need to consider whether the problem can be solved or not.